Cognitive Function of Junior Junior school students in Solving Geometry Problems Based On Verbalizer and Visualizer Cognitive Style - Intan, Paramita; Kurniasari, Ika (Faculty of Mathematics and Natural Sciences, Universitas Negeri Surabaya, 2021)
Abstrak ” Pada penelitian ini, peneliti ingin mengeksplorasi bagaimana fungsi kognitif siswa SMP dalam menyelesaikan masalah geometri ditinjau dari gaya kognitif. Tujuan dari penelitian ini adalah untuk menggambarkan fungsi kognitif siswa SMP menyelesaikan masalah geometri ditinjau dari gaya kognitif yakni gaya kognitif verbalizer dan visualizer. Metode penelitian yang digunakan dalam penelitian ini adalah penelitian deskriptif kualitatif dan menggunakan dua siswa SMP kelas IX di Surabaya sebagai responden yang masing-masing memiliki gaya kognitif verbalizer dan visualizer. Hasil penelitian ini menunjukkan bahwa siswa PRM bergaya kognitif verbalizer berada pada level ketiga (berpikir rasional abstrak) dari fungsi kognitif rigorus mathematical thinking dan subjek telah menerapkan semua fungsi kognitif pada level pertama dengan indikator yang menonjol yaitu pembandingan dimana subjek mencari karakteristik yang sama dan berbeda antara persegi dan persegi panjang dalam menyelesaikan masalah geometri. Sedangkan siswa LDH bergaya kognitif visualizer berada pada level ketiga (berpikir rasional abstrak) dari fungsi kognitif rigorus mathematical thinking dan hanya menerapkan sebagian besar fungsi kognitif pada level pertama dalam menyelesaikan masalah geometri dengan indikator yang menonjol yaitu visualisasi dimana subjek memberikan simbol pada gambar bangun yang disajikan dalam menyelesaikan masalah geometri.Kata kunci: Fungsi kognitif, Gaya kognitif, Masalah geometri, Verbalizer, Visualizer.Abstract ” In this article, we explore how the cognitive function of junior junior school students in solving geometry problems based on cognitive style. The purpose of this study was to describe the cognitive functions of junior junior school students solving geometry problems reviewed from verbalizer and visualizer cognitive style. The research method used in this research is descriptive qualitative research. This research used two students of IX grade in Surabaya as respondents who each student have a cognitive style of verbalizer and visualizer. The results of this study indicate that PRM students with cognitive verbalizer style are at the third level (abstract rational thinking) of the cognitive function rigorous mathematical thinking and the subject has applied all cognitive functions at the first level with a prominent indicator is comparison where the subject looks for the same and different characteristics between square and rectangle in solving geometry problems. Whereas LDH students with cognitive visualizer style is at the third level (abstract rational thinking) of cognitive function rigorous mathematical thinking and apply most cognitive functionsat the first level with a prominent indicator is visualization where the subject provides symbols on the image in solving geometric problems.Keywords: Cognitive function, Cognitive style, Geometry problems, Verbalizer, Visualizer.